A novel deep learning-based method for automatic stereology of microglia cells from low magnification images - Morera, Hunter; Dave, Palak; Kolinko, Yaroslav; Alahmari, Saeed; Anderson, Aidan; Denham, Grant; Davis, Chloe; Riano, Juan; Goldgof, Dmitry; Hall, Lawrence O; Harry, G Jean; Mouton, Peter R (Neurotoxicology and teratology, 2024)
Microglial cells mediate diverse homeostatic, inflammatory, and immune processes during normal development and in response to cytotoxic challenges. During these functional activities, microglial cells undergo distinct numerical and morphological changes in different tissue volumes in both rodent and human brains. However, it remains unclear how these cytostructural changes in microglia correlate with region-specific neurochemical functions. To better understand these relationships, neuroscientists need accurate, reproducible, and efficient methods for quantifying microglial cell number and morphologies in histological sections. To address this deficit, we developed a novel deep learning (DL)-based classification, stereology approach that links the appearance of Iba1 immunostained microglial cells at low magnification (20×) with the total number of cells in the same brain region based on unbiased stereology counts as ground truth. Once DL models are trained, total microglial cell numbers in specific regions of interest can be estimated and treatment groups predicted in a high-throughput manner (<1 min) using only low-power images from test cases, without the need for time and labor-intensive stereology counts or morphology ratings in test cases. Results for this DL-based automatic stereology approach on two datasets (total 39 mouse brains) showed >90% accuracy, 100% percent repeatability (Test-Retest) and 60× greater efficiency than manual stereology (<1 min vs. ∼ 60 min) using the same tissue sections. Ongoing and future work includes use of this DL-based approach to establish clear neurodegeneration profiles in age-related human neurological diseases and related animal models.
Keywords: Animals; počet buněk; Deep Learning; Humans; Cell Count; lidé; deep learning; zvířata; Mice; Microglia; Brain; mikroglie; mozek; myši